2020
DOI: 10.1186/s12885-020-06724-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and survival of pregnancy-associated breast cancer: a retrospective study of 203 cases in China

Abstract: Background: Pregnancy-associated breast cancer (PABC) is an aggressive disease, and since Chinese authority began to encourage childbearing in 2015, the incidence of PABC has increased. This study investigated the characteristics and survival of PABC patients. Methods: Patients with PABC who underwent surgery at Fudan University, Shanghai Cancer Center between 2005 and 2018 were enrolled. Data concerning the tumor characteristics, maternal state (whether first or nonfirst pregnancy) and survival outcome were r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…A study by Harvell et al analyzed the presence of breast cancer subtypes in PABC and found that the presence of Luminal A, Luminal B, Her2-positive, TNBC, and basal-like subtypes in PABC ( 58 ). Other studies also confirmed TNBC, Luminal B and HER2-positive as the most common subtypes among PABC while luminal A subtype was rare ( 25 , 52 , 59 61 ) ( Table 1 ).…”
Section: Introductionmentioning
confidence: 60%
“…A study by Harvell et al analyzed the presence of breast cancer subtypes in PABC and found that the presence of Luminal A, Luminal B, Her2-positive, TNBC, and basal-like subtypes in PABC ( 58 ). Other studies also confirmed TNBC, Luminal B and HER2-positive as the most common subtypes among PABC while luminal A subtype was rare ( 25 , 52 , 59 61 ) ( Table 1 ).…”
Section: Introductionmentioning
confidence: 60%
“…The 11 included studies were from six countries: China (4), South Korea (2), Taiwan (2), Japan (1), India (1) and Saudi Arabia (1). Four studies did not mention whether the PABC patients were diagnosed antepartum or postpartum ( 24 , 26 , 27 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study of PABC patients treated in our hospital from 2005 to 2018 suggested that the incidence of PABC in non-rst-pregnancies was higher than that in rst-pregnancies [7]. However, the correlation between parity and prognosis of breast cancer was unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported that the prognosis of PABC is worse than that of non-PABC [3][4][5][6], but no comparison has been studied regarding parity. A recent retrospective study in our center showed higher incidence of PABC in non-rst-pregnant women than in rst-pregnant women [7]. In this study, we retrospectively analyzed the clinical and pathological characteristics of PABC, and preliminarily explored the correlation between parity and the prognostic factors of breast cancer.…”
Section: Introductionmentioning
confidence: 99%